2020
DOI: 10.1371/journal.pone.0226681
|View full text |Cite
|
Sign up to set email alerts
|

Higher prevalence of splenic artery aneurysms in hereditary hemorrhagic telangiectasia: Vascular implications and risk factors

Abstract: Background Splenic artery aneurysm (SAA) is a rare but potentially fatal condition. Rupture results in 25% mortality up to 75% in pregnant women with 95% fetal mortality. Brief reports suggest an increased risk of developing SAA in patients with HHT. Methods We analyzed enhanced multidetector CT data in 186 HHT patients matched (gender and ± 5 year old) with 186 controls. We screened for SAA and recorded diameter of splenic and hepatic arteries and hepatic, pancreatic and splenic parenchymal involvements. We d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…( 290,294 ) Commonly reported causes include arteriosclerosis and fibromuscular dysplasia. ( 280,290 ) Recently, attention has been drawn to HHT ( 296 ) and the combination of alpha‐1 antitrypsin deficiency and chronic liver disease requiring LT as risk factors. ( 297 ) Pseudoaneurysms of the SA are mostly related to pancreatitis, infection, and trauma.…”
Section: Splenic Artery Aneurysmsmentioning
confidence: 99%
“…( 290,294 ) Commonly reported causes include arteriosclerosis and fibromuscular dysplasia. ( 280,290 ) Recently, attention has been drawn to HHT ( 296 ) and the combination of alpha‐1 antitrypsin deficiency and chronic liver disease requiring LT as risk factors. ( 297 ) Pseudoaneurysms of the SA are mostly related to pancreatitis, infection, and trauma.…”
Section: Splenic Artery Aneurysmsmentioning
confidence: 99%
“…In contrast, thoracoabdominal artery aneurysms accounted for 13.2%, of which splenic artery aneurysms have been reported to account for 4.3%, and are considered to be relatively rare (13). A subsequent large study revealed that 24.7% of patients with HHT had splenic artery aneurysms, which was significantly higher than that in a sex-and age-matched control group (14). The risk factors for the development of splenic artery aneurysms include female sex, older age, multiple pregnancies, and pregnancy.…”
Section: Discussionmentioning
confidence: 95%
“…Regarding arterial malformations, there are other brief reports which suggest the increased risk of developing arterial aneurysms, mainly splenic artery aneurysms (SAA) in patients with HHT [ 20 ]. Sellier et al found a 4.57 higher rate of SAA in their prospective study of 186 HHT patients who were screened with a multidetector CT [ 21 ]. In our case series we also encountered one patient with a splenic artery aneurysm that was successfully treated with embolization ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%